2014
DOI: 10.5713/ajas.2013.13212
|View full text |Cite
|
Sign up to set email alerts
|

Ingestive Behavior of Lambs Confined in Individual and Group Stalls

Abstract: The experiment was conducted to evaluate the ingestive behavior of lambs confined in individual and group stalls. We used thirty-four lambs in their growing phase, aged an average of three months, with mean initial live weight of 17.8±5.2 kg. They were allotted in a completely randomized design with 24 animals kept in individual stalls and 10 animals confined as a group. The experiment lasted for a total of 74 days, and the first 14 days were dedicated to the animals’ adaption to the management, facilities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
0
13
1
Order By: Relevance
“…Animal behavior can be used to indicate quality of the whole production system, including individual activities of the animal in its social and physical environment (Custodio et al, 2017). There is increasing concern about animal welfare and economically viable productive management (Eustáquio Filho et al, 2014). Sheep feedlot is a strategy capable of satisfying both the producer and the consumer, since it allows the carcasses of young animals and, consequently, better-quality products available in the market (Urano et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal behavior can be used to indicate quality of the whole production system, including individual activities of the animal in its social and physical environment (Custodio et al, 2017). There is increasing concern about animal welfare and economically viable productive management (Eustáquio Filho et al, 2014). Sheep feedlot is a strategy capable of satisfying both the producer and the consumer, since it allows the carcasses of young animals and, consequently, better-quality products available in the market (Urano et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that sheep spend 10 h a day in idleness (Ítavo et al, 2008). Studies on the ingestive behavior of sheep confined in stalls (Alves et al, 2010;Silva et al, 2016;Eustáquio Filho et al, 2014) Roberto Ingestive behavior and efficacy of male sheep housed in different stocking densities Costa et al…”
Section: Introductionmentioning
confidence: 99%
“…General inspection showed satisfactory condition of the investigated animals. Gain and development degree of the animal's organism were checked by weighting method [10,11]. Animals division into two groups was based on age, weight factor and other criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of data resulting from the study of the usage of the diet developed for the ewes from the experimental group revealed that the animals remained fleshed and active, and after the lambing an increased milking was evidenced while nursing the lambs. There were no evidenced changes in coat, mucous membranes, and any deviations of chemistry values on the side of vital body systems [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…In this perspective, before replacing a diet with an alternate feed, it is of utmost importance to examine parameters such as feed intake, feeding behavior patterns, blood markers, rumen fermentation, and energy estimation. This would provide a better understanding on how to incorporate the feed into the new diet, understand its nutritive value, and thereby optimize animal production (Van Soest, 1994;Eustáquio Filho et al, 2014;Rodrigues et al, 2014;Mendes et al, 2015). Thus, the objective of this study was to evaluate feeding behavior; physiological, hematological, and biochemical parameters; and rumen fermentation parameters in lactating goats fed diets containing P. platycephala pod meal (PP).…”
Section: Introductionmentioning
confidence: 99%